Does Hypothermic Treatment Provide an Advantage After Spinal Cord Injury Until Surgery? An Experimental Study - Duz, Bulent; Kaplan, Metin; Bilgic, Serkan; Korkmaz, Ahmet; Kahraman, Serdar (Springer/Plenum Publishers, 2009)
We compared the effects of early and late stage hypothermia treatment after spinal cord injury. Five groups each consisting of seven rats were included in this study. In Group 1a (Clip applied-non-treatment group) and Group 1b (Clip applied-treated group) the spinal cords were harvested 1 h after the injury. In Group 2a (clip applied, non-treated group) and Group 2b (clip applied-treated group) the injured segments were harvested 24 h after injury. Group 3 was designed as the sham-operated group. The significantly lower levels of TBARS and GSH-Px in Group 2a, as compared with Group 1b suggests that the hypothermia was effective in the early stage of treatment (P < 0.05). In contrast, TBARS and GSH-Px levels were significantly increased at the 24 h timepoint following treatment (P < 0.05).Short-term systemic hypothermia reduces lipid peroxidation in the early stages after spinal cord injury. This beneficial effect disappears 24 h following systemic hypothermic treatment.
Keywords: Lipid peroxidation; Spinal cord injury; Systemic hypothermia